Hands-on neuroevolution with Python : build high-performing artificial neural network architectures using neuroevolution-based algorithms - Omelianenko, Iaroslav (Packt Publishing, 2019)
This book will help you to apply popular neuroevolution strategies to existing neural network designs to improve their performance. It covers practical examples in areas such as games, robotics, and simulation of natural processes, using real-world examples and data sets for your better understanding.